PEMBERDAYAAN KELOMPOK TERNAK SAIYO SAKATO NAGARI KAMBANG BARAT MELALUI OPTIMALISASI PEMELIHARAAN AYAM KUB DENGAN INOVASI RANSUM LOKAL DAN TEKNOLOGI PENETASAN - Sepri Reski; Ridho Kurniawan Rusli; Linda Suhartati (Jurnal Hilirisasi IPTEKS, 2024)
This activity aimed to empower the Saiyo Sakato livestock group in Nagari Kambang Barat, Kabupaten Pesisir Selatan, by optimising the management of Kampung Unggul Balitbangtan (KUB) chicken with local feed innovation and simpler hatching technology. The main focus was on developing local feed innovation and applying more straightforward hatching technology. The methods used included extension, training, and intensive assistance, with the livestock group being guided in creating a feed formula and demonstrating how to make an egg incubator. The results of this service showed that applying a feed formula containing local feed ingredients such as rice bran, corn, soybean meal, and fish meal could increase the productivity of KUB chickens, significantly reduce feed costs, and replace the use of commercial feed. Furthermore, the creation of egg incubators by members of the livestock group could increase hatching efficiency and contribute to the sustainable increase of the KUB chicken population in Nagari Kambang Barat. In addition, this activity also successfully enhanced the knowledge and skills of the group members in the more professional maintenance of KUB chickens, especially in making local feed formulations and hatching techniques. The high enthusiasm of the group members was evident through their active participation in each training session, the application of the knowledge gained during the activities, and their implementation in the field. The conclusion from this service activity is the increased capacity of the Saiyo Sakato livestock group in the management of KUB chicken maintenance, which not only enhances productivity and efficiency but also supports the sustainability of livestock businesses in the area through the utilisation of local resources and technological innovation. This activity provides a replicable model for empowering livestock groups in other areas with similar conditions.